Altered gene expression profiles in the hippocampus and prefrontal cortex of type 2 diabetic rats - Abdul-Rahman, Omar (BioMed Central, 2012)
BACKGROUND: There has been an increasing body of epidemiologic and biochemical evidence implying the role of cerebral insulin resistance in Alzheimer-type dementia. For a better understanding of the insulin effect on the central nervous system, we performed microarray-based global gene expression profiling in the hippocampus, striatum and prefrontal cortex of streptozotocin-induced and spontaneously diabetic Goto-Kakizaki rats as model animals for type 1 and type 2 diabetes, respectively. RESULTS: Following pathway analysis and validation of gene lists by real-time polymerase chain reaction, 30 genes from the hippocampus, such as the inhibitory neuropeptide galanin, synuclein gamma and uncoupling protein 2, and 22 genes from the prefrontal cortex, e.g. galanin receptor 2, protein kinase C gamma and epsilon, ABCA1 (ATP-Binding Cassette A1), CD47 (Cluster of Differentiation 47) and the RET (Rearranged During Transfection) protooncogene, were found to exhibit altered expression levels in type 2 diabetic model animals in comparison to non-diabetic control animals. These gene lists proved to be partly overlapping and encompassed genes related to neurotransmission, lipid metabolism, neuronal development, insulin secretion, oxidative damage and DNA repair. On the other hand, no significant alterations were found in the transcriptomes of the corpus striatum in the same animals. Changes in the cerebral gene expression profiles seemed to be specific for the type 2 diabetic model, as no such alterations were found in streptozotocin-treated animals. CONCLUSIONS: According to our knowledge this is the first characterization of the whole-genome expression changes of specific brain regions in a diabetic model. Our findings shed light on the complex role of insulin signaling in fine-tuning brain functions, and provide further experimental evidence in support of the recently elaborated theory of type 3 diabetes.